Optimization Techniques For High Performance Content Downloading And Data Access In Vehicular Networks (International Journal of Engineering and Computer Science, 2015)
We consider a road scenario where users in vehicles are well-equipped with communication-enabled interfaces in vehicles are requesting for data access or content downloading from the internet servers or roadside Access Points (APs). Here the content that is requested or downloaded is altogether different content (different from that of the other vehicular users). Downloading an altogether different content from the Internet is a topic of increasing interest in vehicular networks due to high demand of mobile users and vehicular networks. We will analyze the technique used for increasing the performance limits of such vehicular communication system for downloading content and accessing data which is unique for the other users by considering the downloading process as an optimization problem, so that can maximize the overall system throughput by leveraging both Infrastructure-to-Vehicle (I2V) and Vehicle-to- Vehicle (V2V) communication. We will see the various methods used to investigate the impact of various factors such as the traffic intensity of vehicular users in the given region, deployment of roadside infrastructure, V2V relaying technique and penetration rate of the system. Our main objective will be to introduce traffic relaying by one or more vehicles creating a multi-hop between the user and the AP along the roadside so that the data flow is maximize across the whole network using a maximum flow algorithm.